2005
DOI: 10.1038/sj.eye.6701954
|View full text |Cite
|
Sign up to set email alerts
|

Ocular syphilis: the new epidemic

Abstract: Aim To present the clinical presentation, diagnosis, and management of syphilitic uveitis in the context of an epidemic of syphilis in the UK. Method Retrospective clinical case series. Results Six new cases of syphilitic uveitis presented to the Manchester Uveitis Clinic in 2004, after a 15-fold increase in the incidence of syphilis in the UK, including 615 cases in Greater Manchester in the 5 years to 2004. Four cases had secondary syphilis, two had latent disease, two had no rash, and two were HIV positive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 7 publications
3
66
0
2
Order By: Relevance
“…Twenty-five to 50% of patients with ocular syphilis have no other clinical general signs [3,35]. Finally, high-risk sexual behaviors [13], HIV coinfection (33%) [3], or a previous history of syphilis infection (46%) [17] are key elements to guide the diagnosis, as underscored in our study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Twenty-five to 50% of patients with ocular syphilis have no other clinical general signs [3,35]. Finally, high-risk sexual behaviors [13], HIV coinfection (33%) [3], or a previous history of syphilis infection (46%) [17] are key elements to guide the diagnosis, as underscored in our study.…”
Section: Discussionmentioning
confidence: 80%
“…This phenomenon occurred in most European countries and localized outbreaks have been reported, particularly in England [3]. Its incidence also dramatically increased in the United States in the early 2000s [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The highly active antiretroviral therapy (HAART) era has seen an increase in the number of cases of ocular syphilis [9,10], which may be due to a decrease in AIDS-associated mortality [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported on their clinical experience with corticosteroids in ocular syphilis 18,19 but on a smaller scale and not at set time points. Previous studies advised local corticosteroids in case of interstitial keratitis or anterior uveitis 14,20 and systemic corticosteroids in case of profound visual loss, posterior uveitis, 21 scleritis, and optic neuritis. 14,20 Because of our results and recommendations in the literature, we suggest considering adding corticosteroids to antibiotic treatment in all cases of syphilitic uveitis.…”
Section: Corticosteroidsmentioning
confidence: 99%